MLL-AF9 Expression in Hematopoietic Stem Cells Drives a Highly Invasive AML Expressing EMT-Related Genes Linked to Poor Outcome - Stavropoulou, Vaia; Kaspar, Susanne; Brault, Laurent; Sanders, Mathijs A; Juge, Sabine; Morettini, Stefano; Tzankov, Alexandar; Iacovino, Michelina; Lau, I-Jun; Milne, Thomas A; Royo, Hélène; Kyba, Michael; et al. (Cancer cell, 2016)
To address the impact of cellular origin on acute myeloid leukemia (AML), we generated an inducible transgenic mouse model for MLL-AF9-driven leukemia. MLL-AF9 expression in long-term hematopoietic stem cells (LT-HSC) in vitro resulted in dispersed clonogenic growth and expression of genes involved in migration and invasion. In vivo, 20% LT-HSC-derived AML were particularly aggressive with extensive tissue infiltration, chemoresistance, and expressed genes related to epithelial-mesenchymal transition (EMT) in solid cancers. Knockdown of the EMT regulator ZEB1 significantly reduced leukemic blast invasion. By classifying mouse and human leukemias according to Evi1/EVI1 and Erg/ERG expression, reflecting aggressiveness and cell of origin, and performing comparative transcriptomics, we identified several EMT-related genes that were significantly associated with poor overall survival of AML patients.